Association between mother’s purchase intention of iron-fortified infant cereal and iron intake among children aged 6-23 months in Tangerang, Indonesia - Simatupang, Yustina Rossa; Chandra, Dian Novita; Khusun, Helda; Februhartanty, Judhiastuty; Iswarawanti, Dwi Nastiti; Sari, Okky Lupita (World Nutrition Journal, 2025)
Background: Iron deficiency can lead to anemia, negatively impacting children's cognitive and physical development. Mothers' knowledge of iron and the benefits of fortified complementary foods may have influenced their purchase intentions and decisions. Objective: This study aimed to investigate the association between mothers' purchase intentions, actual purchases of iron-fortified infant cereals, and iron intake in children aged 6–23 months in Tangerang, Indonesia. Research on this topic remained limited, emphasizing the need for further studies to strengthen the existing evidence. Methods: This study employed a cross-sectional design involving 162 mothers in pairs with their children aged 6–23 months, recruited consecutively. Data were collected using validated questionnaires. Data analysis was performed using the non-parametric Mann-Whitney test to compare groups and Spearman's correlation test to assess the strength of relationships between variables. A p-value < 0.05 was considered statistically significant. Results: Mothers showed positive attitudes and intentions towards purchasing iron-fortified cereals, with a notable 51.9% having made recent purchases. While these purchase intentions correlate with actual purchases, they did not directly influence children's iron intake. Instead, factors such as mother’s education, occupation, and household income played significant roles in determining iron intake levels. Conclusion: Purchase intentions were associated with actual purchase intention; however, factors such as gender, mother’s education, occupation, and household income did not exhibit a direct relationship with children's iron intake. This study indicates that while mother’s purchase intentions are associated with actual purchases, they do not directly impact children's iron intake.